INTENSITAS SERANGAN RAYAP PADA Eucalyptus pellita DI AREAL HUTAN TANAMAN INDUSTRI PT. WANA HIJAU PESAGUAN KABUPATEN KETAPANG - Simanjuntak, Octo Erwin; Suryantini, Rosa; Nurhaida, . (Universitas Tanjungpura, 2019)
PT. Wana Hijau Pesaguan developed the Eucalyptus plant in 2017 and had one year old (2017-2018). Observations Eucalyptus in PT. Wana Hijau Pesaguan was found termites that attacked Eucalyptus tree (Research and Development 2007). One of termites spesieses that had been indentified by this company is Coptotermes curvignathus. However, until now there had not been known intensity of attacks and the level of damage on the Eucalyptus by termies. Besides there was also the lack of scientific information and publications relating to the level of damage and damage by termites in this area.This research aimed to count the intensity of termite attack in E. pellita in PT. Wana Hijau Pesaguan. This research was conducted from August to September 2018 using field survey. Plot samples were taken as many as 24 plots of size 20 x 20 m, the sampling intensity was 10% of the area of 9.4 ha. Data analysis in this study used analysis of the level of damage and intensity of the attack. The results showed this, the species of termites that attacked the E. pellita was Macrotermes gilvus. The level of attack were 0 - 9.25% with the average of damage intensity reached 3.21%. It was categorized into mildly damaged. The factors that influenced the occurrence of termite attacks were the amount of trash and wood stumps, trenches, and locations bordering rubber plants and forests around plants.Keywords: Eucalyptus pellita, the intensity of damage, the level of attack, Termite, Macrotermes gilvus